Spatial-temporal relationship of surface temperature with the type of cover and land use, in the neighborhoods of the municipality of Paracatu, Mina Gerais, Brazil - dos Santos, Arthur Pereira [UNESP]; Simionatto, Henzo Henrique [UNESP]; Arantes, Leticia Tondato [UNESP]; Salas, Angie Paola Santacruz [UNESP]; da Cunha e Silva, Darllan Collins [UNESP] (Universidad Complutense de Madrid (UCM), 2024)
This work addresses the influence of the type of vegetation cover on soil, measured through the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Built-up Index (NDBI), with the variation of Surface Temperature (LST) in the neighborhoods of the municipality of Paracatu, Minas Gerais (Brazil). Landsat-5 and 8 satellite images were used, and the calculations showed that the variation of LST is related to the suppression of vegetation due to urban expansion. This elimination is responsible for the specific neighborhood of Bom Pastor (28) presenting the highest variation in the average LST over the years. The vegetative factor was also responsible for the Jardim Europa neighborhood (47) revealing a lower fluctuation in the average of this parameter, highlighting the importance of these results for urban management purposes.
Relación espacio-temporal de la temperatura superficial con el tipo de cobertura y uso del suelo, en los barrios del municipio de Paracatu, Mina Gerais, Brasil
Relation spatio-temporelle de la température de surface avec le type de couverture et l'utilisation des terres, dans les quartiers de la municipalité de Paracatu, Mina Gerais, Brésil
Keywords: NDBI; NDVI; Urban expansion; Vegetative factor